Migration, Resilience, Vulnerability and Migrants’ Health (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
In recent times, particularly during the 21st century, there have been significant increases and changes in international migration and resettlement patterns due to factors such as people’s ability to travel, ease of communication and technology, and civil unrest and conflicts. Global populations have increased and integrated across settings, challenging the differentiation between types of migrants, such as refugees (those migrating because of factors such as civil unrest, wars, persecution, or other vulnerability) and economic migrants. This mixture of migration and resettlement patterns will continue for generations due to these diverse, multicultural, and complex communities and we will need more research to provide evidence to inform nations and global responses to any emergences. This Special Issue of the International Journal of Environmental Research and Public Health focused on the migration, resilience, and vulnerability and general migrants’ health accepted original research papers, case reports, reviews, and conference papers. Articles dealing with new approaches to address issues, including migration (opportunities, challenges, and vulnerability), migrants’ health, settlement, and migrant health-care service access and specific migrants’ subgroups were also accepted. Other manuscript types including methodological papers, position papers, policy briefs and reports, and commentaries were sought. We accepted manuscripts from different disciplines, including public health, social and behavioural sciences, anthropology, epidemiology, psychology, and demography. This reprint compiles 30 publications.